CDKN2A Gene Mutations: Implications for Hereditary Cancer Syndromes - Anastasiia Danishevich; Airat Bilyalov; Sergey Nikolaev; Nodirbec Khalikov; Daria Isaeva; Yuliya Levina; Maria Makarova; Marina Nemtsova; Denis Chernevskiy; Olesya Sagaydak; Elena Baranova; Maria Vorontsova; et al. (Biomedicines, 2023)
Malignant neoplasms, including pancreatic cancer and melanoma, are major global health challenges. This study investigates melanoma pancreatic syndrome, a rare hereditary tumor syndrome associated with CDKN2A gene mutations. CDKN2A mutations contribute to a lifetime risk of melanoma ranging from 28% to 67%. This study reports the clinical features of six individuals with CDKN2A mutations and identifies recurrent alterations such as c.307_308del, c.159G>C and c.71G>C. It highlights the need for CDKN2A mutation testing in suspected cases of familial atypical multiple mole melanoma. Clinically significant variants show associations with melanoma and pancreatic cancer. The challenges of treating individuals with CDKN2A mutations are discussed, and the lack of specific targeted therapies is highlighted. Preclinical studies suggest a potential benefit of CDK4/6 inhibitors, although clinical trials show mixed results. This study underscores the importance of continued research into improved diagnostic and therapeutic strategies to address the complexities of hereditary cancer syndromes.